Intermittent versus continuous intraperitoneal glycopeptide/ceftazidime treatment in children with peritoneal dialysis-associated peritonitis - Schaefer, Franz; Klaus, Günter; Müller-Wiefel, Dirk E.; Mehls, Otto (Journal of the American Society of Nephrology, 1999)
Abstract. Intermittent intraperitoneal antibiotic administration appears as a practical and economical therapeutic concept in continuous peritoneal dialysis (CPD)-related peritonitis, but the equivalence of this principle with standard continuous treatment awaits confirmation by prospective, randomized clinical trials. This study evaluates the efficacy, safety, and clinical acceptance of an initial combination treatment including a glycopeptide (vancomycin or teicoplanin) and ceftazidime, each applied either intermittently or continuously, in a cohort of pediatric patients with CPD-related peritonitis. Patients randomized for continuous treatment received an intraperitoneal loading dose of glycopeptide and ceftazidime followed by maintenance doses added to each dialysate bag. In the intermittent treatment groups, the glycopeptide was administered in two loading doses 7 d apart, and ceftazidime during one dialysis cycle per day. Initial treatment response was evaluated after 60 h by the change in a Disease Severity Score and by the clinical decision to continue initial treatment. Of 152 patients observed for a total of 234 patient years, 90 patients developed 195 episodes of peritonitis (including 27 relapses within 4 wk after end of treatment). Dialysate cultures were positive in 83% of the episodes. In Gram-positive peritonitis (79% of culture-positive cases), the primary success (overall 95%) and relapse rates (21%) were not different between continuous and intermittent, or between vancomycin and teicoplanin treatment. Oversensitivity reactions occurred in three and ototoxicity in one vancomycin-treated patient, whereas no such side effects were observed with teicoplanin. Residual renal function declined during peritonitis episodes regardless of treatment modality. In Gram-negative peritonitis (18% of cases), intermittent ceftazidime treatment was less successful than continuous treatment according to clinical judgment (3 of 11 versus 10 of 14, P < 0.05), but not when rated by Disease Severity Score (8 of 11 versus 12 of 14). In conclusion, intermittent and continuous intraperitoneal treatment of CPD-related peritonitis with glycopeptides and ceftazidime is equally efficacious and safe when measured by objective clinical criteria. This contrasts with a strong tendency of clinicians to move from intermittent to continuous treatment in severe peritonitis.